2016
DOI: 10.17533/udea.rccp.v29n2a05
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian estimates of genetic parameters for reproductive traits in Nellore cows raised on pasture in tropical regions

Abstract: Estimación bayesiana de parámetros genéticos para características reproductivas en vacasNelore bajo pastoreo en condiciones tropicales Summary Background: Nellore cows are well adapted to tropical conditions, and they have good maternal ability as well as long and prolific reproductive life. Objective: to estimate (co)variances and genetic parameters for calving interval (CI), age at first calving (AFC), gestation length (GL), and days open (DO) in Nellore cows. Methods: covariance components and genetic param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 19 publications
2
9
1
1
Order By: Relevance
“…The genetic correlation of 0.04 between GL and AFC was in agreement with other preceding studies [4,15]. Gestation length was estimated to have moderate negative genetic correlations with DO and low positive correlations with CI.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The genetic correlation of 0.04 between GL and AFC was in agreement with other preceding studies [4,15]. Gestation length was estimated to have moderate negative genetic correlations with DO and low positive correlations with CI.…”
Section: Discussionsupporting
confidence: 91%
“…Cavani et al [3] and Buzanskas [9] reported low heritability estimates for AFC of 0.10 in Brahman cattle and 0.04 in Canchim beef cattle. In Nellore cows, heritability estimates of 0.11 [10], 0.17 [11], 0.25 [12], and 0.36 [4] for AFC were described in various previous works. Van der Westhuizen et al [13] reported a moderate heritability estimate of 0.40 for AFC in multi-breed beef cattle herd.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zebu cattle ( Bos taurus indicus ) is highly diffused in Brazil, because of its rusticity and high adaptation to the Brazilian climate conditions. Nellore is the major Zebu beef cattle breed used as purebred and in crossbreeding‐based systems, presenting good performance throughout the national territory (Magnabosco, Lopes, Rosa, & Sainz, ).…”
Section: Introductionmentioning
confidence: 99%